Entrepreneurship and Regional Development: The Role of Family and Extended Family Networks in Nigeria - Ahamefule, Ikechukwu Cosmas (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2025)
This paper examines the critical role of family and extended family networks in fostering entrepreneurship and regional development in Nigeria. Drawing on qualitative case studies and comparative analysis, the study explores how kinship-based entrepreneurial models—such as the Igbo apprenticeship system (Igba Boi), Yoruba family manufacturing clusters, and Hausa trading cooperatives—contribute to economic resilience, job creation, and localized growth. While these networks provide essential social capital, access to informal financing, and intergenerational knowledge transfer, they also face challenges including governance deficiencies, succession conflicts, and resistance to innovation. The paper highlights policy gaps and proposes actionable recommendations to strengthen family-based entrepreneurship while integrating modern business practices. By bridging indigenous kinship systems with formal institutional support, Nigeria can harness the full potential of family networks for sustainable regional development.